Odpowiedź:
^2 - do kwadratu
I: x
II: x+2
III: x+4
I+II+III=596
x^2 + (x+2)^2 + (x+4)^2 = 596
x^2 + x^2 + 4x + 4 + x^2 + 8x + 16 = 596
3x^2 + 12x + 20 - 596 = 0
3x^2 + 12x - 576 = 0
x^2 + 4x - 192 = 0
a = 1 b = 4 c = -192
delta = b^2 - 4ac
delta = 4^2 - 4 × 1 × (-192)
delta = 16 + 768
delta = 784
pierwiastek z delty = 28
x1 = (-b - pierwiastek z delty) / 2a
x1 = (-4 - 28) / 2
x1 = -32/2
x1 = -16
x2 = (-b + pierwiastek z delty) / 2a
x2 = (-4 + 28) / 2
x2 = 24/2
x2 = 12
I: 12
II: 12 + 2 = 14
III: 12 + 4 = 16
Szczegółowe wyjaśnienie:
chyba dobrze